(untitled) (Research, Society and Development, 2022)
Pharmaceutical care is the set of actions performed by the pharmacist, in collaboration with other health professionals, which aim to promote the rational use of medicines and the maintenance of treatment effectiveness and safety. Hypertension is a cardiovascular disease of high prevalence among the population, characterizing a significant risk factor for morbidity and mortality. Faced with this problem, many patients with hypertension use medicinal plants for treatment, based on empirical knowledge. However, the misuse of medicinal plants, regardless of their origin, can cause problems such as: alterations in blood pressure, drug interactions, damage to the central nervous system, liver, and kidneys, which can lead to hospitalization and even death, depending on how they are used. In view of this problem, pharmaceutical care in the use of medicinal plants is of great relevance to avoid possible undesirable effects. The aim of this study was to identify and report the importance of pharmaceutical care in the use of medicinal plants in patients with systemic arterial hypertension. The present work is a literature review with consultation in SciELO, PubMed, LILACS and Google academic databases. During the search, 44 articles were selected in Portuguese and English, published in the last five years. Also, 10 medicinal plant species were selected that contain drug interactions and antihypertensive potential. Based on the results presented, we conclude that the use of medicinal plants in the treatment of systemic arterial hypertension, when oriented and accompanied by the professional pharmacist, is very safe and effective.